2012
DOI: 10.1073/pnas.1215806109
|View full text |Cite
|
Sign up to set email alerts
|

Direction-selective retinal ganglion cells arise from molecularly specified multipotential progenitors

Abstract: Single progenitors can give rise to any and all of the main retinal cell types: photoreceptors, interneurons (horizontal, bipolar, and amacrine cells), retinal ganglion cells (RGCs), and glia. Many of these types are divisible into multiple functionally, structurally, and molecularly distinct subtypes (e.g., ∼25 for RGCs). It remains unknown when and how progenitors become committed to generate such subtypes. Here, we determine the origin of RGCs that respond selectively to vertical motion and express cadherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…6 I, J, and N). In contrast, another RGC subtype, the On-Off direction-selective RGCs (dsRGCs), labeled by anti-CART (cocaine-and amphetamineregulated transcript) staining (22), exhibited only a 33% loss, which was similar to the extent of total RGC loss ( Fig. 6 K, L, and O).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…6 I, J, and N). In contrast, another RGC subtype, the On-Off direction-selective RGCs (dsRGCs), labeled by anti-CART (cocaine-and amphetamineregulated transcript) staining (22), exhibited only a 33% loss, which was similar to the extent of total RGC loss ( Fig. 6 K, L, and O).…”
Section: Resultsmentioning
confidence: 80%
“…Interestingly, the onecut factors seem to promote certain subtypes but repress others. The generation of RGC subtypes has just begun to be studied (22) and the molecular markers for most RGC subtypes remain to be identified; therefore, we do not yet have a full picture of how Oc1 and Oc2 regulate RGC subtype formation. However, the many RGC genes identified in our RNASeq analysis, which are expressed in only subsets of RGCs, provide new opportunities for further studying the mechanisms underlying RGC subtype formation.…”
Section: Potential Mechanisms By Which Oc1 and Oc2 Function In Multiplementioning
confidence: 99%
“…A similar principle operates in the vertebrate retina, where subtypes of RGCs and amacrine cells-identified by their physiological light responses, neurotransmitter phenotypes, or gene expression profiles-have stereotyped dendritic projections to IPL sublayers (Figure 4a) (Famiglietti & Kolb 1976, Siegert et al 2009, Wässle 2004. RGC and amacrine subtype fate choices, including laminar-targeting decisions, are correlated with and likely specified by birthdate (Cherry et al 2009, De la Huerta et al 2012, Osterhout et al 2014, Voinescu et al 2009). A few transcription factors controlling laminar choice have been identified, but none of these alter IPL stratification without changing other aspects of cell fate, such as neurotransmitter type (Cherry et al 2011, Kay et al 2011.…”
Section: Dendrite Targeting Is Determined Geneticallymentioning
confidence: 92%
“…A single progenitor, however, can also produce two distinct neuronal subtypes (14)(15)(16)(17). In some instances, neurons of the same functional subtype may also share a common progenitor (18), but their generation may involve both symmetric and asymmetric divisions (13,19,20). Recent retroviral studies in chick retina revealed the presence of two cell clones comprising the same horizontal cell (HC) type (H1 HC) and larger clones with even numbers of H1 and H3 HCs (11).…”
mentioning
confidence: 99%